THE INFLUENCE OF SOCIAL MEDIA INTERACTION ON VISITING DECISION IN INDONESIA (CASE STUDY: SURVEY TO ACTIVE FOLLOWERS OF FOLK INDONESIA INSTAGRAM ACCOUNT) - Sujawoto, Fitra Ananta; Hartanto, Wishnu; Fernanda, Ahmad Irvan; Nur, Salsadila Aisah; Suhada, Salsabila Mutiara (Jurnal Industri Parawisata, 2025)
This study was prepared with the aim of knowing how much influence Instagram social media interactions have on the visiting decisions of followers of the Indonesian Folk account (@folkindonesia) in Indonesian tourist destinations. The approach used is a quantitative approach with a purposive sampling data collection method, which was conducted by distributing questionnaires to 144 active followers of Folk Indonesia accounts who meet the criteria. Data analysis was conducted using simple linear regression analysis.Â  The results showed that Social Media Interaction (X) that occurs on Folk Indonesia accounts has an influence on Visiting Decision (Y) of 62.2%. Thus, the results show that the most common reason for following Folk Indonesia is because they like the uploads, which is shown through the quality of the visual content (photos and videos) uploaded. This in turn plays a role in influencing the visiting decision made by its followers.